PENGARUH MARKETING MIX TERHADAP LOYALITAS PELANGGAN DI WARUNG MAKAN TIP TOP KELURAHAN SAOMBO KECAMATAN GUNUNGSITOLI KOTA GUNUNGSITOLI - Peringatan Harefa (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
In this study, the formulation of the problem "Is there an Effect of Marketing Mix on Customer Loyalty in TIP TOP Restaurant, Saombo Village, Gunungsitoli District, Gunungsitoli City?"This research aims: a. to find out and obtain data about the implementation of the marketing mix carried out at the TIP TOP Restaurant, Saombo Village, Gunungsitoli District, Gunungsitoli City. b. to find out and obtain data about customer loyalty at TIP TOP Restaurant, Saombo Village, Gunungsitoli District, Gunungsitoli City. c. to find out how much influence the marketing mix has on customer loyalty at the TIP TOP Restaurant, Saombo Village, Gunungsitoli District, Gunungsitoli City.The sample in this study was taken from the entire population of 97 people, the method used in this research is quantitative research methods (Inferest), where the data collected is verified, validated, and tested for the hypothesis using the t test.Processing data distribution t with dk = 95 and a significant level of 5% obtained t table = 1.661. Thus, tcount>ttable (10.626>1.661), with a correlation coefficient of 0.737.The results obtained by testing the coefficient of determination are 54%, the effect of the marketing mix on customer loyalty, while other factors that are not discussed in this study are 46%. Based on the results of hypothesis testing, Ha is accepted and Ho is rejected, indicating that tcount>ttable (10.626>1.661), so it can be said that there is an effect of marketing mix on customer loyalty at TIP TOP Restaurant, Saombo Village, Gunungsitoli District, Gunungsitoli City.